A purging procedure for pantoprazole and 4-lumen catheters to prevent IV drug incompatibilities - Bertsche, Thilo; Veith, Carolin; Stahl, Alexander; Hoppe-Tichy, Torsten; Meyer, Franz Joachim; Katus, Hugo; Haefeli, Walter E. (Pharmacy world & science, 2010)
Objective of the study The purpose of this prospective intervention study was to assess the number of patients with Y-site incompatibilities before and after implementation of quality improvement measures to prevent incompatibilities consisting of a focused instruction for pantoprazole as a drug frequently involved in incompatible drug pairs and of a recommendation to use 4-lumen instead of 3-lumen catheters to increase the number of available central infusion lines. Setting Cardiovascular intensive care unit where several standard operating procedures (SOPs) dealing with compatibility were already in place. Method In a prospective intervention study, patients’ IV medication was assessed for potential incompatibilities using a database containing compatibility information on approximately 60,000 drug pairs. In a first period, routine administration was monitored in 53 consecutive patients (control group). Then, quality improvement measures were implemented recommending a purging procedure before and after bolus administration of pantoprazole as a drug frequently causing incompatibilities in this setting. Additionally, the use of 4-lumen instead of 3-lumen catheters was suggested whenever considered useful by the responsible physicians. The monitoring was repeated during a second period in another 58 patients consecutively admitted to the same unit (intervention group). Main outcome measure Overall number of patients with at least one incompatible drug pair and number of patients receiving incompatible pantoprazole combinations. Results The number of patients receiving incompatible pantoprazole combinations decreased from 15 of the 15 patients receiving pantoprazole (100.0%) in controls to 9/16 (56.2%) in the intervention group (P < 0.01). The overall number of patients with incompatibilities was not influenced by the intervention with 36/58 (62.1%) compared to controls with 38/53 (71.7%, P = 0.28). The fraction of central lines contributed by four lumen central catheters was larger due to the intervention (80/168 lines, 47.6%) compared to controls (16/184, 8.7%, P < 0.001). Only sporadically there were incompatible combinations of drugs governed by the already existing SOPs. Conclusion In an intensive care setting with good SOP adherence, purging before and after administration decreased the respective incompatibility rate whereas the use of 4-lumen instead of 3- lumen catheters had not the expected benefit on separating drug pairs.
Gesehen am 27.01.2023